Epitope mapping of polyclonal clotting factor VIII-inhibitory antibodies using phage display - Mühle, Christiane; Schulz-Drost, Stefan; Khrenov, Alexey V.; Saenko, Evgueni L.; Klinge, Jens; Schneider, Holm (Thrombosis and Haemostasis, 2004)
Clotting factor VIII (fVIII)-inhibitory antibodies represent a major problem in the treatment of haemophilia A. To understand the inactivation mechanisms and to pave the way towards modifications of recombinant clotting factors that reduce their immunogenicity, the exact localization of immunodominant epitopes is required. Here, a random peptide phage display library was employed to identify epitopes of polyclonal fVIII antibodies isolated from patient’s plasma by affinity chromatography. FVIIIbinding specificity and inhibitory activity of the isolated fVIII antibodies were confirmed by ELISA and Bethesda assays. Phage selection on the individual samples yielded several phages which were displaced from binding to the respective antibody preparation by fVIII. Their homology with amino acid motifs of human fVIII and immunoprecipitation results with radioactively labelled fVIII fragments suggested putative epitopes in the A1, A2 and C1 domains of fVIII for one and in the C2 domain for another patient. Synthetic peptides corresponding to the A2, C1 and C2 domain epitopes blocked antibody binding to fVIII and partially neutralized the inhibitory activity of the respective plasma in Bethesda assays. These results provide the proof of principle that random peptide libraries can be used for the mapping of epitopes in a polyclonal antibody preparation.
Keywords: Haemophilia; inhibitor; polyclonal antibodies; epitope mapping; phage display